Accessibility, transportation cost, and regional growth: a case study for Egypt. Issue 2 (3rd July 2017) - Elshahawany, Dina N.; Haddad, Eduardo A.; Lahr, Michael L.
Abstract : This paper focuses on a proposed development corridor in Egypt, a main component of which is a desert-based expansion of the current highway network. The main beneficial features of this proposed transport investment are travel time reductions and improved accessibility. We use a spatial computable general equilibrium (SCGE) model to estimate the economic impacts of changes in transportation costs from this new roadway. To effect this, we integrate the model with a stylized geo-coded transportation network to estimate the spatial distribution of changes in transportation costs. Ignoring the cost of the infrastructure itself, we employ a series of simulations to estimate the likely structural economic impacts that such a large investment in transportation could enable through a series of simulations. Results show the Corridor causes the economic tide to rise for the economies of all Egyptian governorates. Gains in efficiency are particularly strong for those regions that are presently most isolated, namely those located to the southern and western extremes of the country. This suggests that the project will lessen regional disparities across Egypt's governorates. We therefore show that integrated SCGE models can be useful in estimating the potential economic benefits of transportation projects in developing nations like Egypt. Moreover, it is clear that interregional economic models can be vital in examining the varied spatial distribution of the benefits that derive from geographically targeted government spending.